Analysis on Relationship between Accurate Poverty Alleviation and Stock Price Collapse Risk from the Perspective of Information Disclosure. (21st December 2021) - Lin, Chuan; Zhai, Haomiao
Abstract : Accurate poverty alleviation (APA) is crucial to building a well-off society in an all-round way. Companies and the capital market are implementers of APA. In the context of stock price collapse risk (SPCR), this paper verifies whether the APA by state-owned listed enterprises (SOLEs) could effectively suppress SPCR. Empirical results show that SOLEs engaging in APA and investing heavily in APA have a relatively low SPCR. This conclusion holds after the control of robustness and endogenous factors. Information disclosure system mediates the effect of APA on SPCR. Besides, APA suppresses SPCR more significantly in central state-owned enterprises (SOEs) and public welfare SOEs. Further analysis indicates that good institutional environment, strong poverty alleviation pressure, poverty experience of executives, and model of party organization governance can effectively enhance the influence of APA on SPCR. The research results suggest that SOLEs actively engaging in APA can effectively suppress SPCR by disclosing APA information. This is an organic manifestation of APA effectiveness in the capital market.